The Sian Incident A Pivotal Point in Modern Chinese History - Wu, Tien-wei (Michigan Monographs In Chinese Studies, 2020)
In these proceedings, they bring those discussions to a wider audience. Question and answer sessions at the conference were necessarily short and a few speakers delivered abbreviated remarks; this volume restores a number of omissions, and provides additional answers to some pertinent questions put by the audience. The Center hopes to encourage the serious problem-solving these complex issues demand. Far too much time has been spent trying to fix the blame.